Two new genera of epigean harvestmen (Opiliones, Stygnopsidae) from Oaxaca, Mexico, with an identification key for the stygnopsine genera - Cruz-López, Jesús A.; Francke, Oscar F. (Zootaxa, 2020)
Two new genera, Ampliphallus gen. nov. and Guelaguetzia gen. nov., are described from material collected in the state of Oaxaca, Mexico. The genus Ampliphallus gen. nov. is monotypic and contains the species A. chimalapaensis sp. nov., from the tropical rain forest of Santa María Chimalapa, Oaxaca. The genus Guelaguetzia gen. nov. is composed of two species: G. cuicateca sp. nov. (type species) and G. serrana sp. nov., from pine forests in northern Oaxaca. These genera can be recognized from each other mainly by the armature of leg IV and by the male genitalia; both are also compared with the remaining members of the Stygnopsinae. An identification key for all genera of the subfamily is provided.